2020
DOI: 10.1097/cce.0000000000000164
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Use After Cardiac Surgery

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Matebele al have reported that 4% albumin exposure after cardiac surgery is not significantly associated with hospital mortality but has been associated with significant morbidity (bleeding, tamponade, return to theatre, and increased ICU and hospital LOS) and higher adjusted ICU and hospital costs. 14 A randomized controlled trial is required to determine whether albumin use is effective and safe in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Matebele al have reported that 4% albumin exposure after cardiac surgery is not significantly associated with hospital mortality but has been associated with significant morbidity (bleeding, tamponade, return to theatre, and increased ICU and hospital LOS) and higher adjusted ICU and hospital costs. 14 A randomized controlled trial is required to determine whether albumin use is effective and safe in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative bleeding following cardiothoracic procedures remains an important concern with multiple avenues of investigation continuing to assess factors predisposing and potentially influencing the severity of this adverse event. Recent areas of interest include: development of new antifibrinolytic agents to reduce bleeding; 31 measurement of platelet function to reduce bleeding and mortality; 32 single or dual agent antiplatelet therapy to maximize bypass graft patency, but increase postoperative bleeding; 33 36 direct linkage of postoperative cardiac surgical bleeding with increased cost; 4 , 5 safe and efficacious use of postoperative fibrinogen concentrates; 37 , 38 role of patient blood management in reducing blood product transfusion and improving cardiac surgical outcomes; 39 , 40 transfusion reductions associated with the use of prothrombin complex concentrate; 41 , 42 morbidity associated with reoperation for bleeding following cardiac surgery; 3 , 43 , 44 methods of employing thromboelastometry (ROTEM) during cardiac surgery; 45 , 46 contribution of albumin/gelatin to postoperative bleeding; 47 49 advantages of anticoagulation management using thromboelastography (TEG) during cardiopulmonary bypass; 50 52 benefit of thrombin inhibitors for pediatric VAD anticoagulation; 53 , 54 reduction of postoperative blood loss using Unilastin as an antifibrinolytic agent; 55 , 56 and blood loss leading to multisystem organ failure and hematologic complications following LVAD insertion. 7 , 57 …”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in adjusted mortality between those who did or did not receive albumin (adjusted OR, 1.24; 95% CI, 0.56 to 2.79; P = 0.6). 74 More recent prospective studies in cardiac surgical patients have reported improved clinical outcomes, although sample sizes have generally been small, and a risk of publication bias prevails. The 20% Human Albumin Solution Fluid Bolus Administration Therapy in Patients After Cardiac Surgery (HAS-FLAIR) study was a singlecentre, open-label pilot which included 100 consecutive cardiac surgical patients requiring volume resuscitation or improvement in cardiac index in the first 24 postoperative hours.…”
Section: Methodsmentioning
confidence: 99%